A comparative study between cerviprime gel and misoprostol for induction of labour in term pregnancy with unfavourable Bishop’s score: a randomised controlled clinical trial - Sirsam, Shyamkumar; Singh, Alka; Karale, Vivek; Ajmera, Ankush; Nangia, Aishwarya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Induction of labor (IOL) is a common obstetric intervention performed when benefits outweigh risks of continuing pregnancy. Cervical ripening using prostaglandins like dinoprostone (cerviprime) and misoprostol improves induction outcomes. This study compared their efficacy in term pregnancies with unfavorable Bishop’s score, evaluating induction and need for augmentation. Methods: This randomized controlled clinical study was conducted over 18 months in the department of obstetrics and gynecology at a tertiary care centre among 100 term pregnant women (≥37 weeks) with an unfavourable Bishop’s score requiring induction of labour. Participants were randomized into two groups: 50 received intravaginal misoprostol (25μg, repeated every 4 hours) and 50 received intracervical dinoprostone gel (0.5 mg, repeated every 6 hours). Results: A total of 100 pregnant women were studied, divided between the cerviprime and misoprostol groups. The mean age was comparable (33.09±9.56 years vs. 32.54±9.57 years). The time from induction to initiation of labour was significantly shorter in the misoprostol group (≤6 hours in 82% versus 58%; p<0.05). Vaginal delivery occurred in 84% of misoprostol cases and 76% of cerviprime cases. Misoprostol significantly shortened the induction-delivery interval (p<0.02). Oxytocin augmentation was required less often with misoprostol (46% versus 60%; p=0.16). Conclusions: Vaginal misoprostol demonstrated greater efficacy than intracervical dinoprostone gel (cerviprime) for labour induction in term pregnancies with unfavourable Bishop’s scores, achieving shorter induction-to-delivery intervals without increasing maternal or neonatal complications, making it a safe and effective alternative.